THE INCLUSION AND ACCESS TO HEALTH IN SUS BY THE LOOK OF ACADEMIC OF ODONTOLOGY (CIPEEX, 2022)
THE MAIN OBJECTIVE OF THIS WORK WAS TO POINT OUT THE IMPORTANCE AND THE FRUITS OF THE VALORIZATION OF THE PRINCIPLES OF THE UNIFIED HEALTH SYSTEM, WHICH EMPHASIZE THE INCLUSION AND DEVELOPMENT OF EQUITABLE PRACTICES FOR THE CARE OF THE POPULATION, TARGET OF THE SUS INTERNSHIP OF THE COURSE OF DENTISTRY OF THE UNIVERSITY CENTER OF ANÁPOLIS. THE DENTISTRY SCHOLAR HAS IN HIS TRAINING, AS A TRANSFORMING HEALTH AGENT, AN INCREASING NEED TO DEVELOP ASPECTS THAT THENCE THE INCLUSION OF THE POPULATION, FACILITATING ACCESSIBILITY, THIS THAT GOES FAR BEYOND THE GEOGRAPHIC BARRIER, INCLUDING ORGANIZATIONAL, SOCIAL, CULTURAL AND ECONOMIC DIFFICULTIES. IT IS ALSO DELIMITED THE INDISPENSABLE IMPORTANCE OF KNOWLEDGE AND APPLICABILITY OF PRINCIPLES THAT ENSURE EQUITY IN THE CARE PERFORMED IN THE SUS, WITH THE ULTIMATE GOAL OF REACHING THE INDIVIDUAL AND THEIR NEEDS TAKING INTO ACCOUNT EACH PARTICULARITY OF ITS EXISTENCE. THE EXPERIENCE OF STUDENTS IN THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS-UNIEVANGLICA WAS ANALYZED IN A QUALITATIVE WAY, AT THE STAGE PERFORMED IN BASIC HEALTH UNITS OF THE CITY OF ANÁPOLIS. THE STUDENTS HAD THE OPPORTUNITY TO REPORT, THROUGH THE FOLLOWING QUESTION "WHAT IS YOUR PERCEPTION ABOUT THE ACCESS AND INCLUSION OF PATIENTS IN THE UNIFIED HEALTH SYSTEM FROM THEIR EXPERIENCE IN THE INTERNSHIP?", THEIR EXPECTATIONS, FRUSTRATIONS, DESIRES AND VISIONS BESIDES THE COLLECTION OF PHOTOGRAPHS THAT POINTED OUT THE PERSPECTIVE ON THE IMPORTANCE AND EFFECTIVENESS OF THE PRINCIPLES ADOPTED BY THE SUS, REGARDING THE INCLUSION AND ACCESS TO HEALTH CARE. EIGHT TESTIMONIES WERE COLLECTED FROM ACADEMICS FROM THE SEVENTH AND EIGHTH PERIOD OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS WHO HAD ALREADY PARTICIPATED IN THE INTERNSHIP IN THE UNIFIED HEALTH SYSTEM, ALONG WITH THE PHOTOS WERE COPILATED IN A VIDEO THAT WAS REPRODUCED DURING THE V CULTURAL EXHIBITION OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS. IT WAS NOTED THAT IN A GOOD WAY ACADEMICS HAVE A POSITIVE VIEW ON ACCESS AND INCLUSION TO HEALTH AND THAT THEY ARE CAPABLE OF, THE DEPARTURE OF EXPERIENCE OBTAINED IN THE INTERNSHIP, REPRODUCE THE GUIDING PRINCIPLES OF THE SUS. IT IS ALSO FELT THE NEED FOR INVESTMENTS AND IMPROVEMENTS, HOWEVER, THE SUS REPRESENTS A BREAKTHROUGH FOR BRAZILIAN HEALTH, REACHING THE POPULATION IN A SIGNIFICANT WAY. IT IS CONCLUDED THAT PARTICIPATING IN THE SUS INTERNSHIP DEMONSTRATES TO THE STUDENTS HOW VALUABLE AND RICH ARE THE PRINCIPLES ADOPTED BY THE FAMILY HEALTH STRATEGY, WHICH ALLOW ACCESS TO HEALTH WITHOUT DISCRIMINATION, REACHING THE MARGINALIZED POPULATION, AND WHO HAS THEIR RIGHTS OFTEN HINDERED BY OBSTACLES, WHETHER THESE ARE PHYSICAL, ECONOMIC, CULTURAL OR SOCIAL.KEYWORDS:UNIFIED HEALTH SYSTEM. HEALTH SERVICES ACCESSIBILITY. HEALTH CARE QUALITY, ACCESS, AND EVALUATION.